Comments on Evaluation of Endoscopic Findings and Detection of H. pylori Antibody by Serum IgG ELISA - Islam, MDU; Rahman, SHZ; Shamsuzzaman, SM; Muazzam, N; Chowdhury, A; Sarkar, AR (Faridpur Medical College Journal, 2011)
Bangladesh is a developing country with high prevalence of peptic ulcer disease and H. pylori infection. During the period of January 2007 to December 2007, a cross sectional study was conducted. In this study, serum samples were collected from 86 dyspeptic patients undergoing upper GIT endoscopy to determine anti-H. pylori IgG antibody by serum ELISA and was evaluated with endoscopic findings. Out of 86 study patients, gastro-duodenal mucosa was found normal in 58.14%, gastritis in 11.63%, duodenitis 2.33%, reflux oesophagitis 4.65%, peptic ulcer 17.44% and carcinoma of stomach 5.81%. Among 86 study population, 68 were serum IgG ELISA positive and 20 were negative. Key words: H. pylori; IgG; ELISA; Non-ulcer dyspepsia. DOI: 10.3329/fmcj.v6i1.7406 Faridpur Med. Coll. J. 2011;6(1): 24-27